Pesnik in glasbenik - Novak-Popov, Irena (Jezik in slovstvo, 2014)
The article provides an analysis of new forms of interaction between poetry and music that have become established in recent times as intermedia events. Particular attention is devoted to poets who express a lasting interest in sonic qualities, whether in titles, motifs, life philosophy or in the musically motivated composition of poetic texts. The article also describes various multimedia projects and music-poetry events that have been recorded at alternative cultural venues and are accessible on sound media or as videos transferred to the Internet.
Keywords: Čučnik, Primož, 1971-; Podlogar, Gregor, 1974-; Škrjanec, Tone, 1953-; Vrečar, Tomislav, 1976-; Polič, Andraž, 1972-; Slovene literature; slovenska književnost; slovenska poezija; slovenski pesniki; intermedialnost; zvočnost; 18.-21. st.